3′-deoxytubercidin: A potent therapeutic candidate for the treatment of Surra and Dourine - Kayhan Ilbeigi; Dorien Mabille; Rajdeep Roy; Mirco Bundschuh; Ewout Van de Velde; Fabian Hulpia; Serge Van Calenbergh; Guy Caljon (International Journal for Parasitology: Drugs and Drug Resistance)
Surra and Dourine are widespread diseases caused by two protozoan parasites Trypanosoma brucei evansi and Trypanosoma brucei equiperdum, respectively. A wide range of animals including camels, horses, cattle and buffaloes are susceptible to infection. These diseases pose a significant socio-economic burden, primarily due to the limited therapeutic options and the complications associated with toxicity and drug resistance, making disease management particularly challenging. This study evaluated the potential of 3′-deoxytubercidin, a previously identified antitrypanosomal nucleoside, as a therapeutic candidate for Surra and Dourine using mouse models. Mice infected with either T. b. evansi or T. b. equiperdum were treated with 3′-deoxytubercidin at a dosage of 6.25 mg kg−1 administrated intraperitoneally once daily for five consecutive days. The treatment resulted in full cure, as confirmed by both microscopic examination and quantitative PCR, without any observed toxicity. Given the importance of considering the One Health concept in developing new antiparasitic drugs for veterinary use, the environmental impact of 3′-deoxytubercidin was assessed through the ecotoxicity tests on aquatic organisms, conducted in accordance with OECD guidelines. The compound showed some toxicity to Daphnia (EC50 = 0.54 mg L−1 in acute Daphnia test) but had no significant adverse effects on green alga at concentrations tested (up to 50 mg L−1). This study confirms the suitability of 3′-deoxytubercidin as an effective and safe therapeutic candidate for further development in the treatment of Surra and Dourine, highlighting its potential for improving disease management in affected regions.